2009
DOI: 10.1073/pnas.0903613106
|View full text |Cite
|
Sign up to set email alerts
|

Human genetic deficiencies reveal the roles of complement in the inflammatory network: Lessons from nature

Abstract: Complement component C5 is crucial for experimental animal inflammatory tissue damage; however, its involvement in human inflammation is incompletely understood. The responses to Gram-negative bacteria were here studied taking advantage of human genetic complement-deficiencies-nature's own knockouts-including a previously undescribed C5 defect. Such deficiencies provide a unique tool for investigating the biological role of proteins. The experimental conditions allowed cross-talk between the different inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
141
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 120 publications
(156 citation statements)
references
References 28 publications
14
141
0
1
Order By: Relevance
“…It also mediates phagocytosis and recognizes a broad range of different microbial molecules (57). In humans, upregulation of CD11b on monocytes and granulocytes is differentially dependent on CD14 and C5a, but combined inhibition of both pathways is required for sufficient ablation in both cell types (22,23). In pilot experiments, we have observed a pronounced upregulation of wCD11R3 within 60 min after induction of E. coli sepsis in the current model.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It also mediates phagocytosis and recognizes a broad range of different microbial molecules (57). In humans, upregulation of CD11b on monocytes and granulocytes is differentially dependent on CD14 and C5a, but combined inhibition of both pathways is required for sufficient ablation in both cell types (22,23). In pilot experiments, we have observed a pronounced upregulation of wCD11R3 within 60 min after induction of E. coli sepsis in the current model.…”
Section: Discussionmentioning
confidence: 62%
“…The significance of complement was recently shown in a model of E. coli-induced sepsis in baboons, as complement inhibition displayed broad anti-inflammatory effects, partially reversed microcirculatory dysfunction, and prevented systemic blood pressure from falling (21). Additionally, ex vivo whole blood studies on humans have shown that oxidative burst, upregulation of adhesion molecules, expression of TF, and granulocyte enzyme release are, to a large extent, complement-ependent in Gram-negative-induced inflammation (22,23). Notably, the inhibitory effect on a broad spectrum of Gram-negative-induced inflammatory mediators is reinforced by a combined inhibition of complement and CD14 (24).…”
mentioning
confidence: 99%
“…It has been suggested that C5 deficiency increases the susceptibility to meningococcal infections in humans (31), and C5 deficiency in mice is associated with increased bacteremia in a CLP peritonitis model (32). In vitro assays using whole blood from patients with C5 deficiency suggested that C5 is essential for bacterial killing and that C5a is required in bacterial phagocytosis and oxidative burst production by up-regulating CR3 (CD11b/CD18) on leukocytes (33). Other studies report that C5 inhibition with antibodies reduced the bacterial load in the blood and organs and provided protection against CLP-induced sepsis in rats with a genetic deficiency of C6, which can generate C5a and C5b but not C5b-9 (18).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines may, however, indirectly contribute to complement activation, e.g., by increasing the expression of anaphylatoxin receptors (38). High levels of C5a may also inhibit neutrophils (39) and regulate the transcription of cytokines (40,41). The interplay between different parts of the innate immune response in neonates merits further investigation.…”
Section: Articlesmentioning
confidence: 99%